DINAMIKA UKURAN PERUSAHAAN, ARUS KAS, DAN PROFITABILITAS SEKTOR INDUSTRI MAKANAN DAN MINUMAN DI INDONESIA - Suwandi, Suwandi; Eka, Andi Primafira Bumandava; Nurdiani, Elia Erna; Lambyombar, Yustinus; Rosari, Renya (POLITEKNIK LP3I JAKARTA, 2026)
Profitability is often a problem in every important corporate policy decision. Company size and cash flow are thought to impact profitability. This causal study aims to measure the effect of company size and cash flow on the profitability of the food and beverage sector in the Indonesian capital market for the 2020-2024 period. This research covers 9 sample companies selected using a purposive sampling approach. The financial statements included in this study were obtained through the website www.idx.co.id using a documentary approach. After data collection, analysis was conducted using multiple linear regression. The findings indicate that company size has an insignificant negative effect on company profitability, while cash flow has an insignificant positive effect. Following these findings, efficient asset management and cash management optimization are needed to achieve optimal profitability.